A study on work from home in education industry due to COVID-19. (29th October 2020) - Kaur, Rajwinder; Kaur, Gagandeep
Due to COVID-19, all the service sectors are performing work from home model. Work from home model in education industry is introduced for the first time. So education industry experienced benefits and challenges of work from home for the first time. The study is conducted to know these benefits and challenges faced by faculties in education industry. For the study, faculties from different colleges and universities are selected randomly to fill the data. The data for the study is taken from colleges and universities of different districts of Punjab. The findings of the study state that in education industry there are many benefits and challenges of work from home. Benefits of work from study include no office distractions, reduced office politics and future demand of digital study platforms and challenges include schedule and time issues, communication issues, coordination issues, hectic schedule, etc. The paper also put light on the suggestions which are recommended by the faculties of colleges and universities for the improvement of work from home in education industry.